CRITICAL SUCCESS FACTORS IN ONLINE LANGUAGE LEARNING - Alberth Alberth (TEFLIN Journal: A publication on the teaching and learning of English, 2011)
Abstract: With the proliferation of online courses nowadays, it is necesÂsary to ask what defines the success of teaching and learning in these new learning environments exactly. This paper identifies and critically discusses a number of factors for successful implementation of online delivery, particularly as far as online language learning is concerned. These include student and teacher characteristics, instructional design, provision of support to instructors and students, technology, and lanÂguage skills characteristics. I argue that these factors need to be care-fully considered when designing online language learning simply be-cause they could potentially impinge on students learning and learning experience in these new learning environments.